2008
DOI: 10.1007/s00234-008-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Global and focal cerebral perfusion after aneurysmal subarachnoid hemorrhage in relation with delayed cerebral ischemia

Abstract: Introduction The pathogenesis of delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH) is unclear. We assessed whether DCI relates to focal or global cerebral perfusion on admission and on follow-up imaging. Materials and methods Twenty-seven SAH patients underwent computed tomography (CT) perfusion (CTP) on admission and at clinical deterioration or 1 week after admission in clinically stable patients. We compared global and focal (least perfused territory) perfusion in patients with DCI (n=12),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…Although the mean age for DCI subjects in this study (53 years) was lower than the mean age for DCI subjects in some studies (59 years) [17, 18], it was similar to mean age for DCI subjects (54 years) and overall SAH population (52 years) in other studies [9], and we saw no between-group difference. We did not find a relationship between DCI and other demographic characteristics (Table 2) which is consistent with the literature [8, 13].…”
Section: Discussionsupporting
confidence: 49%
“…Although the mean age for DCI subjects in this study (53 years) was lower than the mean age for DCI subjects in some studies (59 years) [17, 18], it was similar to mean age for DCI subjects (54 years) and overall SAH population (52 years) in other studies [9], and we saw no between-group difference. We did not find a relationship between DCI and other demographic characteristics (Table 2) which is consistent with the literature [8, 13].…”
Section: Discussionsupporting
confidence: 49%
“…Eight of the nine studies using quantitative assessments reported mean perfusion values [6][7][8][10][11][12]15,16 and one gave the lowest values in predefined regions of interest (ROIs). 17 In six studies, all ROIs were used in the analyses, 7,10,12,[15][16][17] whereas two other studies only used the ROIs with lowest CBF or CBV and highest MTT or TTP. 6,8 Of these last two studies, we obtained additional information on the mean values of all ROIs together and included these values in the quantitative analyses.…”
Section: Resultsmentioning
confidence: 99%
“…6,11,17 CT Perfusion and Prediction of Delayed Cerebral Ischemia Four studies with 153 patients investigated the relationship between perfusion on admission and later development of DCI. 7,8,10,13 Three studies determined CBF, CBV, MTT, and TTP quantitatively (Table 2, Figure 2). 7,8,10 Cerebral blood flow, CBV, MTT, and TTP on admission did not differ between patients who later developed DCI and those who did not develop DCI.…”
Section: Resultsmentioning
confidence: 99%
“…Perfusion deficits are described as focal regions of reduced CBF and/or prolonged MTT. However, global perfusion abnormalities have also been observed in patients with DCI [14]. Few studies in the literature have evaluated CTP using DCI defined as clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%